A Judicial Analysis of the Need for Medical Dispute Court in Resolving Health Disputes - Ramadhanti, Dita Annisa; Lany, Arman (LifeSciFi, 2025)
Medical disputes in Indonesia are handled through fragmented mechanisms such as disciplinary bodies, mediation, and general courts, resulting in overlapping authority, lengthy procedures, and legal uncertainty due to the absence of a specialized forum with integrated legal and medical expertise. This study aims to analyze the legal basis and urgency of establishing a Medical Dispute Court following the enactment of the Health Law of 2023. Using a normative juridical method with statutory, conceptual, and case approaches, this research examines relevant constitutional provisions and the new health legislation. The findings reveal that the establishment of a Medical Dispute Court has a strong foundation in the 1945 Constitution and the Health Law of 2023, and is urgently needed to ensure legal certainty, substantive justice, and balanced protection of rights. These findings imply that the establishment of a specialized Medical Dispute Court is a strategic policy instrument to integrate fragmented dispute resolution mechanisms, enhance legal certainty, and ensure balanced legal protection for patients and medical professionals within Indonesia’s health law system.